Local Mineral Clays, Characterization and Application in Petroleum Refining - R. A. Buker; M. Z. Hamoodat (College of Education for Pure Sciences, 2012)
Abstract The study includes preparation and characterization of Mineral clay catalysts from local and natural mineral clays, which have been applied in purification and fractionation of heavy crude oils. The studied samples were collected from area around Mosul city /Iraq. Physical properties were investigated to characterize the clay samples in addition to their solubility in many acids. Meanwhile, classical chemical analysis and X-Ray fluorescence were applied to determine their chemical composition. Moreover, X-Ray diffraction, thermal analysis, and infrared spectroscopy have been used to study their structural properties. Such investigations spot the light on the prepared sample to be active and selective in term of the adsorption chromatography. Qaiyarah heavy crude oil was fractionated into its simple and useful components which have been characterized via infrared spectroscopy.